Correlations of microstructure and mechanical properties of the ternary Sn-9wt%Zn-2wt%Cu solder alloy - Silva,Bismarck Luiz (2018)
The microstructure length-scales (dendritic and eutectic), morphologies and tensile properties of a ternary Sn-9wt.%Zn-2wt.%Cu alloy are compared with those of a binary eutectic Sn-9wt.%Zn alloy. The following experimental/analytical steps were performed: transient directional solidification experiments of the Sn-9wt.%Zn-2wt.%Cu alloy; measurements of secondary dendrite arm (λ2) and interphase spacing (λ); morphology of the eutectic α-Zn phase; determination of thermal parameters such as cooling rate (ṪL) and their evolutions during solidification; and, finally, interrelations of microstructure vs. tensile properties. The addition of 2wt.%Cu causes significant refinement of the eutectic structure. Hall-Petch type experimental expressions outlined the variations of strength and ductility with both λ2 and λ. Very fine Zn globules and needles forming the eutectic in the ternary alloy seems to cause a reversal on ductility behavior, as compared to the tendency observed for the binary Sn-9wt.%Zn alloy. Here, for the ternary Sn-9wt.%Zn-2wt.%Cu alloy ductility increases with decreasing interphase spacing.